SAE Technical Paper Series 2001
DOI: 10.4271/2001-01-2883
|View full text |Cite
|
Sign up to set email alerts
|

New Investigations of the Mechanisms of Lightning Strike to Radomes Part I : Experimental Study in High Voltage Laboratory

Abstract: The main purpose of the experiments described here is the analysis of the mechanisms of radome protection with lightning diverters of various types and sizes. A high voltage arrangement and associated diagnostics have been implemented to perform a quantitative study of the inception and propagation mechanisms of the corona and leader discharges that precede the final breakdown. It is shown that ambient humidity plays a significant role on the discharge process and that the nature of the discharge initiated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…It can be observed that the electric field at the radome base decreases by 50 % if 6 solid diverter strips of 0.4m length were installed on the radome surface. This is in good agreement with the measurements (Ulmann et al, 2001). a) side view b) view from top …”
Section: Electric Field Shielding Effect Of Stripssupporting
confidence: 93%
See 2 more Smart Citations
“…It can be observed that the electric field at the radome base decreases by 50 % if 6 solid diverter strips of 0.4m length were installed on the radome surface. This is in good agreement with the measurements (Ulmann et al, 2001). a) side view b) view from top …”
Section: Electric Field Shielding Effect Of Stripssupporting
confidence: 93%
“…In high ambient humidity conditions (>60%), the radome becomes moderately conductive because of humidity absorption at its surface (Ulmann et al, 2001;Delannoy et al, 2001). Although this decreases the internal field due to shielding effect, it also reduces the efficiency of the strips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low ambient air humidity, the radome is perfectly insulating. Therefore, the field measured at the internal electrode [1] is lowered only by the presence of the diverter strips through three different effects that appear in sequence during the voltage rise:…”
Section: Discharges From Diverter Stripsmentioning
confidence: 99%
“…The mechanisms of inception and propagation of corona and leader discharges around a radome, equipped with 4 diverter strips and an internal electrode representing the radar, are described in a companion paper [1]. The radome is located in a plane to plane gap submitted to an impulse voltage.…”
Section: Introductionmentioning
confidence: 99%